A case study of the audience at three art music concert in Malaysia - Loo, Fung Chiat (Universiti Putra Malaysia Press, 2009)
The development of art music and the construction of acoustically designed concert halls in Malaysia have provided more opportunities for live performances of various genres of art music. Generally, full attention is given to performers and their performances at a live concert, however it should be noted and emphasized that a live concert will not take place without the existence of its spectators. Unlike pop concerts, the size of audience at art music concerts is often small and this has become a key concern among organizers. The present study was carried out to identify the characteristics of the Malaysian audience at eight performances of three selected art music concerts: a concert version opera, a symphony concert, and a musical. A survey was used and interviewers intercepted potential respondents after each concert. Respondents were either interviewed or requested to complete the same survey questions themselves. A total of 660 samples were gathered. Based on the analysis on the respondents’ occupations, it was found that they were mostly students and were generally below 30 years old. There was a balance between those with and without music background among the respondents. Musical was found to be the most preferred genre among the seven music genres given to the respondents. The results of this survey could function as a preliminary examination for future research to trace the changing characteristic of audience over time.